Hyperemesis Gravidarum-induced Encephalopathy, Gagal Ginjal, dan Kematian Janin – Laporan Kasus: Laporan Kasus - Risqiyani, Siti Zulaikha; Hapsari, Fikhy Rizky (Cermin Dunia Kedokteran, 2026)
Introduction: Hyperemesis gravidarum (HG) is a severe form of nausea and vomiting during pregnancy that can become life-threatening for the mother and fetus if not treated properly. Although most cases resolve with conservative management, rare instances progress to severe multisystem complications, including encephalopathy, acute kidney injury, and fetal demise. Case: A 22-year-old G1P0A0 woman at 13 weeks of gestation presented with decreased consciousness following four weeks of intractable vomiting since 8 weeks of pregnancy. The patient has been vomiting more than five times a day, and consciousness began to decrease over the last two days, with complaints of blurry vision and tremors. Physical examination revealed hypotension (blood pressure 80/45mmHg), tachycardia, and cold extremities. Laboratory findings demonstrated acute kidney injury (serum creatinine 8.1 mg/dL), severe electrolyte disturbances (sodium 115.7 mmol/L, potassium 2.07 mmol/L, chloride 77.8 mmol/L), and hepatocellular injury. Transabdominal ultrasound confirmed fetal demise at 13 weeks of gestation. Discussion: HG can precipitate life-threatening complications, including Wernicke's encephalopathy, acute kidney injury, and fetal loss through mechanisms of severe dehydration, malnutrition, and electrolyte imbalance. Early recognition with aggressive fluid resuscitation, electrolyte correction, and nutritional support is essential to prevent irreversible multisystem deterioration and improve maternal-fetal outcomes. Conclusion: Multisystem complications in HG are extremely dangerous for both mother and fetus. Appropriate preventive measures and early intervention must be taken to prevent worsening outcomes and reduce the risk of maternal and fetal mortality.